332 Effect of Chemical and Biological Preservatives on in vitro Fermentation and Methane Production of Ensiled and Aerobically Exposed Wet Brewer's Grains. (8th October 2021) - Killerby, Marjorie A; Zamudio, Diego; Ames, Kaycee; Henry, Darren D; Schwartz, Thomas; Robinson, Anna; Oppong, Godloves M; Romero, Juan Jose J
Abstract: This study evaluated the effects of preservatives on the in vitro fermentation measures of wet brewer's grain (WBG) silage at different stages of storage. Treatments (TRT) were sodium lignosulfonate at 1% (NaL1) and 2% (NaL2; w/w of fresh WBG), propionic acid (PRP; 0.5% w/w of fresh WBG), a combination inoculant (INO; Lactococcus lactis and Lactobacillus buchneri each at 4.9 log cfu/fresh WBG g), and untreated WBG (CON). WBG (Fresh) were packed into 8.8 L mini-silos and stored for 60 d at 21°C (Ensiled), then they were opened and aerobically exposed for 10d (AES). Samples from each stage of storage (STG; Fresh, Ensiled and AES) were analyzed for in vitro ruminal digestibility (24 h).Gas kinetics were recorded using the Ankom RF Gas Production System. Data were analyzed as a randomized complete block design (5 blocks) with a 5 (TRT) × 3 (STG) factorial arrangement. Apparent in vitro DM digestibility (DMD) decreased across STG, (51.5, 47.2 and 40.9 for Fresh, Ensiled and AES, respectively) and increased for NaL1, NaL2 and PRP (~47.8) vs. CON (43.0 ± 2.12%). PRP increased apparent in vitro OM digestibility (OMD) when Ensiled (54.5) and NaL2 increased it for AES (47.1) vs CON (46.3 and 39.9 ± 1.73%, respectively). The asymptotic maximal (M) and rate (k) of gas production decreased across STG (214.6, 181.5, 155.1 and 14.6, 12.6, and 9.8, for Fresh, Ensiled and AES, respectively). PRP increased (200.0) and NaL1 decreased (169.3) M vs. CON (183.9± 7.81ml/incubated DM g), while NaL1 and NaL2 (~11.4) decreased k vs. CON (13.4 ± 0.85%/h). Methane concentration and yield were higher in Fresh vs. other STG (0.94 vs. ~0.84 ± 0.07mM and 0.27 vs. ~0.23 ± 0.03mmol/g fermented OM). Spoilage of WBG decreases fermentability and methane production while PRP and NaL improve digestibility with the former also increasing M and k.